Major diseases affecting neonatal calves (Research, Society and Development, 2019)
The objective of this study was to report the diseases that occur in calves up to one year of age, establishing the main epidemiological factors associated with the occurrence of these diseases. The breeding phase is considered the most sensitive of the entire production system. Calves, especially in the first weeks of life, are more susceptible to acquiring diseases, being important attention by the caregivers on basic care, thus avoiding the highest mortality rates that occur mainly until the weaning, with the most frequent problems being navel infections, diarrhea, pneumonia, verminoses and parasitic sorrows. In view of the above, this study made it possible, through analyzes of scientific studies, to conclude that neonatal care is extremely necessary to prevent the animal from being affected by some type of illness, environmental conditions and inadequate sanitary management associated to the lack of measures prophylactic factors are determinant for the increase in the number of sick animals. On the other hand, the correct nutritional management, prevention and control of these diseases favor to improve health, allowing the animal to express its maximum potential for production and reproduction throughout its life, contributing to a positive economic return, reducing expenses with treatments and with future epidemics.